After the bust: The outlook for macroeconomics and macroeconomic policy - Thomas I. Palley (Levy Economics Institute of Bard College, 2009)
Change was the buzzword of the Obama campaign, in response to a political agenda precipitated by financial turmoil and a global economic crisis. According to Research Associate Thomas Palley, the neoliberal economic policy paradigm underlying that agenda must itself change if there is to be a successful policy response to the crisis. Mainstream economic theory remains unreformed, says Palley, and he warns of a return to failed policies if a deep crisis is averted. Since Post Keynesians accurately predicted that the US economy would implode from within, there is an opportunity for Post Keynesian economics to replace neoliberalism with a more successful approach. Palley notes that there is significant disagreement among economic paradigms about how to ensure full employment and shared prosperity. A salient feature of the neoliberal economy is the disconnect between wages and productivity growth. Workers are boxed in on all sides by globalization, labor market flexibility, inflation concerns, and a belief in small government that has eroded economic rights and government services. Financialization, the economic foundation of neoliberalism, serves the interests of financial markets and top management. Thus, reversing the neoliberal paradigm will require a policy agenda that addresses financialization and ensures that financial markets and firms are more closely aligned with the greater public interest.
Keywords: 330; Finanzmarktkrise; Wirtschaftskrise; Makroökonomik; Konjunkturpolitik; Wirtschaftsliberalismus; Kritik; Postkeynesianismus; Theorie